Testing the Characteristics of the Dose Calibrator Radiation Measurement Tool using Technetium-99m and Cobalt-57 at the Nuclear Medicine Installation at RSUD A. W. Sjahranie Samarinda - Fahira Mutya Mutmainna; Retno Zurma; Pratiwi Sri Wardani; Erlinda Ratnasari Putri (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
A dose Calibrator is one of the dosimeters used to measure radionuclide activity before being given to patients. In order to function as a radiation dosimeter, the dose calibrator must have several good dosimeter properties, such as precision and stability. To test the dose calibrator, a source used by the hospital is required. The dose calibrator used in Instalasi Kedokteran Nuklir RSUD A. W. Sjahranie Samarinda is Capintec 25R. Two of the isotopes are widely used in nuclear medicine, namely Tc-99m and Co-57. The first step of this research was the elution performed by radiopharmaceuticals, then measured background activity. Then, Tc-99m and Co-57 activity were measured. Then, Tc-99m and Co-57 activity were measured for precision and stability tests, finally, graphs were made and evaluated. Based on the research results on the precision test, it was found that the measurement results for the Tc-99m source were obtained at 0.305%, while the result for measuring the activity of the standard Co-57 source was obtained at 0.307%. In the stability test, the result of measuring the Tc-99m source obtained a value of 0.563%, while the result of measuring the activity of the standard Co-57 source obtained a value of 0.437%. It can be concluded that the Capintec CRC 25R in RSUD A. W. Sjahranie Samarinda has good characteristics and performance so the measurement results can be trusted.